Utilization pattern of Internet use among undergraduate students of medical college in New Delhi - Setu, Dr. Yachna; Mehra, Dr. Ridhi (Innovative Journal of Medical and Health Sciences, 2024)
Introduction: Internet is important to college students, especially for professional studies students like medical or engineering who massively uses Internet for academic or research purposes. However, they can’t control or reduce the duration of Internet use in-spite of the negative consequences like health issues, sedentary behaviour. This present study aims to determine the prevalence of Problematic Internet use (PIU), factors associated with PIU among medical students and its health implications. Methods: A descriptive cross-sectional study was performed among 179 medical students. Predesigned, semi-structured questionnaire was used for data collection focussing on Internet use pattern, reasons of Internet use, health issues related to excessive Internet use, and prevalence of PIU was assessed by Dr. Kimberly Young’s internet addiction test (IAT) scale. Result: According to Dr. Kimberly Young’s internet addiction test (IAT) scale, majority of the students have mild Internet addiction (42%)and as IAS (Internet addiction score) ≥50 is considered as PIU (Problematic Internet use) which is 48/179 (26.81%) in present study.PIU was associated with Internet browsing, health issues, online games and education status of both parents. It was observed that most of the students were using Internet for socializing (90.5% ) and Internet browsing (89.9%) followed by academic/education purpose (81.1%), payment of bills (79.9%). The preferred mode of socializing was whats app (57%) followed by whats app + telegram (12%). News feed, Google browsing, watching OTT content, online games were found to be positively associated with PIU (odds ratio >1). Conclusion: Internet addiction is a relatively frequent phenomenon among medical students. The predictors of internet addiction were Internet browsing, health issues, online games and education status of both parents.